PENINGKATAN PRESTASI BELAJAR MATEMATIKA SISWA DENGAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM INVESTIGATION BERBANTU LEMBAR KERJA SISWA DENGAN PENDEKATAN OPEN ENDED SMP NEGERI 2 CEPER KLATEN - Maratu Shalikhah; Aji Permana Putra (Program Studi Pendidikan Matematika, STKIP Bina Bangsa Getsempena, 2018)
The purpose of this class action research is to (1) improve students' mathematics learning achievement through the Group Investigation learning model with the help of worksheet open ended approach in class VII F SMPN 2 Ceper, Ceper District, Klaten Regency 2017/2018 Academic Year. (2) Describe how to overcome the constraints of applying the Group Investigation learning model with the help of worksheet open ended approach to improve mathematics learning achievement of class VII F SMPN 2 Ceper. Based on the results of the study it can be concluded: (1) The application of the Group Investigation learning model with the help of worksheet open ended approach can improve the learning achievement of grade VII F SMPN 2 Ceper, which is indicated by: students of class VII F as many as 32 students have increased learning achievement that is before action only 53.1% of students study completely, after the action becomes 100%. How to overcome constraints, namely the teacher must be skilled in applying Group Investigation learning model with the help of worksheet open ended approach is: a) reviewing the concepts and basic competencies that students will learn, b) forming heterogeneous study groups both in terms of ability, gender, religion, tribes etc., c) prepare everything about learning as well as possible so that when learning runs smoothly, d) minimize the number of group members so that learning takes place effectively with no passive group members or playing alone during group discussions, e) giving gifts at the best group presentations. Abstrak Tujuan penelitian tindakan kelas ini adalah untuk (1) meningkatkan prestasi belajar matematika siswa melalui model pembelajaran Group Investigationberbantu LKS pendekatan open ended pada siswa kelas VII F SMPN 2 Ceper, Kecamatan Ceper, Kabupaten Klaten Tahun Akademik 2017/2018. (2) Mendeskripsikan cara mengatasi kendala penerapan model pembelajaran Group Investigationberbantu LKS pendekatan open endeduntuk meningkatkan prestasi belajar matematika siswa kelas VII F SMP Ceper 2. Berdasarkan hasil penelitian dapat disimpulkan: (1) Penerapan model pembelajaran Group Investigation LKS untuk pendekatan open ended dapat meningkatkan prestasi belajar siswa kelas VII F SMP Ceper 2, yang ditunjukkan oleh : siswa kelas VII F sebanyak 32 siswa mengalami peningkatan prestasi belajar yaitu sebelum tindakan hanya 53,1% siswa belajar tuntas, setelah tindakan menjadi 100%. Cara mengatasi kendala, yaitu guru harus terampil dalam menerapkan model pembelajaranGroup Investigationberbantu LKS pendekatan open endeddiantaranya adalah: a) meninjau konsep dan kompetensi dasar yang akan siswa pelajari, b) membentuk kelompok belajar yang heterogen baik dari segi kemampuan, jenis kelamin , agama, suku dll, c) mempersiapkan segala sesuatu tentang belajar sebaik mungkin sehingga ketika pembelajaran berjalan lancar, d) meminimalkan jumlah anggota kelompok sehingga pembelajaran berlangsung efektif tanpa anggota kelompok pasif atau bermain sendiri selama diskusi kelompok, e) memberikan hadiah pada presentasi kelompok terbaik. Kata kunci: Investigasi kelompok, LKS pendekatan open ended, prestasi belajar siswa